2011
DOI: 10.1093/eurjhf/hfr063
|View full text |Cite
|
Sign up to set email alerts
|

Are beta2‐agonists responsible for increased mortality in heart failure?

Abstract: AimsPrevious large-scale, retrospective studies have shown increased mortality in heart failure (HF) patients using b2-agonists (B2As). We further examined the relationship between B2A use and mortality in a well-characterized population by adjusting for natriuretic peptide levels as a measure of HF severity. Methods and resultsThis was a retrospective cohort study of patients attending an HF Disease Management Programme with mean follow-up of 2.9 + 2.4 years. Chart review confirmed B2A use, dose and duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 29 publications
3
25
0
1
Order By: Relevance
“…Thus, these data may partly explain why there was no influence of β 2 -agonist use on outcome in our study patients. Bermingham et al10 reported that β 2 -agonist therapy in patients with HF showed no relationship with long-time mortality when adjusted for population differences, including BNP levels, which was in accordance with our results. These findings suggested that β 2 -agonists may be used safely in elderly male COPD patients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, these data may partly explain why there was no influence of β 2 -agonist use on outcome in our study patients. Bermingham et al10 reported that β 2 -agonist therapy in patients with HF showed no relationship with long-time mortality when adjusted for population differences, including BNP levels, which was in accordance with our results. These findings suggested that β 2 -agonists may be used safely in elderly male COPD patients.…”
Section: Discussionsupporting
confidence: 93%
“…Further analysis showed that combination therapy had no influence on all-cause mortality in the fully adjusted model. The results presented here are in line with a large-scale study, which also reported no increased risk of mortality in patients with HF taking both β-blockers and β 2 -agonists 10. Two studies that demonstrated that NT pro-BNP was associated with mortality36,37 were also consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Prescription of bronchodilators in such circumstances is a common strategy, despite the ongoing controversies regarding the hazardous consequences this treatment can exert on morbidity and mortality [1,2]. The anticholinergic and beta 2 agonistic properties of bronchodilators are able to destabilize patients with various heart diseases, even if the latter are covered with beta blockers and other cardioprotective drugs [3].…”
mentioning
confidence: 99%
“…Inhaled bronchodilators are frequently prescribed to patients with various forms of heart disease, when bronchospasm and wheezing coexist. The scenario in which these drugs are more extensively studied, is this of heart failure [1,2]. Harmful effects of bronchodilation related to secondary hypokalemia and arrhythmogenesis is a matter of vivid debate in this setting.…”
mentioning
confidence: 99%